Adapting to climate variability and change in India - Bird, Jeremy; Roy, Srabani; Shah, Tushaar; Aggarwal, Pramod K.; Smakhtin, Vladimir U.; Amarnath, Giriraj; Amarasinghe, Upali A.; Pavelic, Paul; McCornick, Peter G. (2016)
Responding to rainfall variability has always been one of the most critical risks facing farmers. It is also an integral part of the job of water managers, whether it be designing interventions for flood management, improving the reliability of water supply for irrigation or advising on priorities during drought conditions. The conventional tools and approaches employed are no longer sufficient to manage the increasing uncertainty and incidence of extreme climate events, and the consequent effects these have on human vulnerability and food security. To be effective, the technological advances need to be matched with physical, institutional and management innovations that transcend sectors, and place adaptation and responsiveness to variability at the centre of the approach. This chapter examines a number of these challenges and possible solutions at a range of scales, from ‘climate-smart villages’ to national policy, with a focus on Asia and India, in particular.